Konstruksi Pesan Moderasi Beragama Melalui Komik dan Quotes di Media Sosial Instagram @Iqomic - Dony Rano Virdaus (Academic Journal of Da'wa and Communication, 2025)
This study examines religious moderation messages conveyed through comics and quotes shared on the @iqomic Instagram account. In the context of Indonesia's diversity, conveying messages of religious moderation is very important to strengthen tolerance and prevent social conflict. This study uses a qualitative method with a netnographic approach, focusing on comic posts and quotes produced by Iqomic. Data was collected through direct observation of Instagram content, and in-depth analysis was conducted using semiotics theory on @qomic in relation to religious moderation and visual communication. The results of the study show that the delivery of religious moderation values in comics and quotes uses a visual narrative approach, easy-to-understand language, touching illustrations, and criticism of deviant practices in everyday life. These narratives illustrate the fulfilment of indicators of religious moderation. Meanwhile, the @iqomic audience tends to interpret these messages in various ways, including supportive, contrary, and doubtful interpretations. This research shows a novelty that the effectiveness of moderation messages is not only determined by content but also by the logic of interaction and the subjectivity of the audience.